All fiber multiwavelength Tm-doped double-clad fiber laser assisted by four-wave mixing in highly nonlinear fiber and Sagnac loop mirror - Ahmad, Harith; Ahmed, Mahmoud Hazzaa M.; Samion, Muhamad Zharif; Harun, Sulaiman Wadi (Elsevier, 2020)
A four-wave mixing (FWM) based multi-wavelength laser based on a double-cladding thulium-doped fiber laser (DC-TDFL) is proposed and demonstrated. A highly nonlinear fiber (HNLF) in conjunction with a Sagnac loop mirror formed by polarization maintaining fibers (PMFs) is used to induce the FWM effect as well as to mitigate gain-competition in the DC-TDFL. This increases the number of lasing wavelengths that can be generated. Approximately 35, 55, and 68 stable lasing lines are achieved within 10 dB, 20 dB, and 28 dB bandwidths by adjusting the polarization controllers. A uniform channel spacing of 0.38 nm is obtained with minimal wavelength drifts and power fluctuations of 0.056 nm and 2.8 dB. This is, to the best of the author's knowledge, the first demonstration of large numbers of lasing channels in the 1.97μm wavelength region from a DC-TDFL. © 2019